Modern approach to the evaluation of the pharmacokinetics and pharmacodynamics of biosimilar recombinant human insulin and insulin analogues in I phase clinical study - Irina A. Proskurina (Endocrinology Research Centre, 2016)
The quality, pharmacokinetic and pharmacodynamic profiles, safety and immunogenicity must be compared to demonstrate the bio-similarities of recombinant human insulin and insulin analogues. To confirm these bio-similarities in clinical studies, it is necessary to adhere to a multi-phased approach, starting with the pharmacokinetics and pharmacodynamics of the study drugs. In this article, in accordance with modern approaches to drug research, evaluation of the pharmacokinetics and pharmacodynamics of recombinant human insulin and analogues of human insulin (biosimilar drugs) is performed in a double-blind, randomised crossover euglycaemic hyperinsulinaemic clamp study.This article describes the main approaches to the evaluation of the pharmacokinetic and pharmacodynamic parameters of recombinant human insulin preparations and insulin analogues during a euglycaemic hyperinsulinaemic clamp study. The inclusion criteria for the sample selection, design and conditions of the study, methods for the suppression of endogenous insulin, recommendations for doses of drugs, duration of the study and choice of primary and secondary pharmacokinetic and pharmacodynamic parameters for bio-similar insulin products (which depend on the duration of their effects) are described.